REPORT OF THE COMMITTEE ON TEACHING METHODS–PROGRAMED INSTRUCTION. - Brown, Robert O.; Hay, Leon E.; Lunn, H. Nelson; Markell, William; McLaughlin, C.L.; Weber, G. Fred; Mitchell, Wiley S. (The Accounting Review, 1964)
Abstract The article presents a report on teaching methods and programmed instructions in the U.S. During the past few years, in the process of continuing search to discover means for increasing instructional efficiency and for developing new materials to cope with the rapidly expanding demands for additional education and training by a burgeoning number of learners, the experimentation and development of programed learning has received the attention of educators and training directors across the country. Programed instruction has found wide-spread usage in industry and in the armed forces in various aspects of training for specific assignments or tasks, in which predetermined performance levels or behavioral patterns had been established. In numerous situations in both education and industry, programed instruction has proved to be effective, and under some circumstances more so than conventional methods. However, at this time research findings, especially at the college level, are totally inadequate to serve as a basis for making decisions on the adoption of programed learning for use throughout any specific course or program.